2021
DOI: 10.1021/acsami.1c12611
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment-Activated Theranostics Nanozymes for Fluorescence Imaging and Enhanced Chemo-Chemodynamic Therapy of Tumors

Abstract: Chemodynamic therapy (CDT) is widely explored for tumor-specific therapy by converting endogenous H 2 O 2 to lethal •OH to destroy cancer cells. However, •OH scavenging by glutathione (GSH) and insufficient intratumoral H 2 O 2 levels seriously hinder the application of CDT. Herein, we reported the fabrication of copper ion-doped ZIF-8 loaded with gold nanozymes and doxorubicin hydrochloride (DOX) for the chemotherapy and CDT synergistic treatment of tumors with the assistance of tumor microenvironment (TME)-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…To further investigate whether SPFT shows tumor-specific cytotoxicity, we selected HELF normal cells as the control cell lines to compare with HepG2 cells (Figure C,D). As reported, compared with normal tissues and cells, lower pH and higher H 2 O 2 are the two of the important characteristics of tumor tissues and cells. , As shown in Figure C, higher cytotoxicity of SPFT toward HepG2 cells than that toward HELF cells is observed in the dark. This result is attributed to the slightly acidic environment in tumor cells, which can destroy the Fe III -TA shell and then trigger chemodynamic therapy and chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate whether SPFT shows tumor-specific cytotoxicity, we selected HELF normal cells as the control cell lines to compare with HepG2 cells (Figure C,D). As reported, compared with normal tissues and cells, lower pH and higher H 2 O 2 are the two of the important characteristics of tumor tissues and cells. , As shown in Figure C, higher cytotoxicity of SPFT toward HepG2 cells than that toward HELF cells is observed in the dark. This result is attributed to the slightly acidic environment in tumor cells, which can destroy the Fe III -TA shell and then trigger chemodynamic therapy and chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…These outstanding performances of MOF/AuNCs assemblies facilitate the sensitive colorimetric sensing of organophosphorus pesticides (OPs), acetylcholinesterase (AChE), choline oxidase (CHO), glucose, hydrogen peroxide, etc. [ 70 , 71 , 121 123 ].…”
Section: Colorimetric Sensingmentioning
confidence: 99%
“…Chemodynamic therapy is a specific tumor treatment and can make tumor cells sensitive to chemotherapy drugs thus improving the chemo therapy effect (Wang et al,2018). Recent study indicated that a novel theranostics nanozymes can be used for both fluorescence imaging and enhancing chemo-chemodynamic therapy (Figure 6) (Zhao et al,2021).…”
Section: Nanomaterials' Theranostics Application In Multimodality Ima...mentioning
confidence: 99%